(untitled) (Economics and region, 2021)
The article summarizes the main methodological approaches to determining the financial condition of the enterprise, considers the stages of analysis of the financial condition of the enterprise. The main approaches to assessing the financial condition of the enterprise and the development of proposals to improve the methodology of analysis of the financial condition of the enterprise, the assessment of the financial condition of the enterprise to find reserves to increase profitability and strengthen commercial calculation as a basis for stable operation other institutions. A critical assessment of the concept of «financial condition» and its definition by various experts is analyzed. Based on the study of improving the methodology of analysis of the financial condition of the enterprise, it is determined that today the most necessary to improve the financial condition of the enterprise is to improve information and methodological support of the financial condition of the enterprise, development of methodological support for forecasting the financial condition of the enterprise. Content of work at each stage, improvement of forms of financial reporting, which will increase its analytical capabilities, development of methods of comprehensive scoring of the financial condition of the enterprise, which would analyze the state of the enterprise for the optimal set of financial indicators and ratios, improvement of theoretical principles of enterprise information system.